A Capital Accord for Emerging Economies? - Powell, Andrew (World Bank, Washington, D.C., 2013)
The Basel 1988 Capital Accord is arguably the most successful of all recent financial "standards." Although it was designed for internationally active banks in G10 countries, more than 100 countries claim to adhere to it, and many apply the Accord to all banks. Significant changes to this Accord are currently under discussion. The author reviews the current proposals (published in January 2001) from the standpoint of an emerging market. He then addresses how implementation in G10 countries will affect the cost of capital to emerging economies. The new proposals make considerable advances in linking risk and regulatory capital for internationally active banks, especially for their corporate loan book. But the corporate-calibrated internal ratings-based (IRB) approach leads to significant changes in capital requirements and spreads for banks that lend to emerging countries. The author proposes that for sovereign lending, banks should develop internal ratings according to an S&P or Moody's scale, and capital charges be levied at the corresponding weights given by the standardized approach. The author argues that the more detailed and specific the proposals are for G10 internationally active banks, the less relevant the proposals will be for non-G10 countries that wish to implement the new Accord for all banks. Indeed, many emerging countries will implement the 'standardized' approach, in which case, given the limited universe of rated risks, little will change. Alternatively, emerging countries will attempt to implement an IRB approach, but with significant problems implementing and calibrating the parameters-or inappropriate use of G10 calibrations. At the same time, banks in emerging economies remain the most important vehicle for financial intermediation and the appropriate regulation of bank capital one of the most important issues for financial sectors. The author suggests that additional alternatives should be included or, failing that, the time may have come specifically for an Accord for emerging economies.